Day 2 Tue, March 27, 2018 2018
DOI: 10.2118/190481-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Salinity Waterflood and Low Salinity Polymer Injection in the Wara Reservoir of the Greater Burgan Field

Abstract: The Greater Burgan Field, first discovered in 1938, is the second largest oilfield in the world. Production from the Greater Burgan began in 1946 from the Wara reservoir via primary recovery. Recently, field-wide waterflood as a secondary recovery mechanism has been implemented. The current insight on the potential of hybrid low salinity water and polymer flooding in the Greater Burgan is presented. The goal of the Greater Burgan Study team in this enhanced oil recovery (EOR) evaluation program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…These economic constraints motivate companies to perform low-salinity pre-flush to optimize the process. Water pre-flush is commonly used to decrease the salinity of the formation brine, which is expected to improve polymer flooding performance [36,39,41].…”
Section: Pilot Projects Of Polymer Floodingmentioning
confidence: 99%
See 2 more Smart Citations
“…These economic constraints motivate companies to perform low-salinity pre-flush to optimize the process. Water pre-flush is commonly used to decrease the salinity of the formation brine, which is expected to improve polymer flooding performance [36,39,41].…”
Section: Pilot Projects Of Polymer Floodingmentioning
confidence: 99%
“…Recently, the concept of the hybrid EOR method, using combined low-salinity water flooding with polymer flooding, has also shown promising results for oil recovery [41,42]. Low salinity also decreases the salinity of formation brine in a similar manner as pre-flush and polymer flooding and afterward retains good mobility control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional tests were planned for other parts of the Burgan field with reservoir rock containing high clay content to further corroborate the established trend of recovery performance with clay content. In the same giant Burgan oilfield, Al-Qattan et al [226] reported another SWCT tests performed on Wara reservoir considering the radius of investigation of 4.8 m around the wellbore. They documented that low saline brine injection reduced Sor by 3% as compared high saline brine injection.…”
Section: Sandstone Reservoirsmentioning
confidence: 99%
“…Additional tests were planned for other parts of the Burgan field with reservoir rock containing high clay content to further corroborate the established trend of recovery performance with clay content. In the same giant Burgan oilfield, Al-Qattan, et al [197] reported another SWCT tests performed on Wara reservoir considering the radius of investigation of 15.6ft around the wellbore. They documented that low saline brine injection reduced Sor by 3% as compared high saline brine injection.…”
Section: Sandstone Reservoirsmentioning
confidence: 99%